2003
DOI: 10.1634/theoncologist.8-6-531
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Tyrosine Kinases in Cancer

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(102 citation statements)
references
References 44 publications
1
92
0
9
Order By: Relevance
“…Furthermore, gain-of-function mutations in c-kit have been described primarily in leukemias and gastrointestinal stromal tumors (GIST) (26). Two general mechanisms of c-kit activation in malignant cells have been described: acquisition of activating mutations or autocrine or paracrine stimulation of the receptor by its ligand SCF (27).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, gain-of-function mutations in c-kit have been described primarily in leukemias and gastrointestinal stromal tumors (GIST) (26). Two general mechanisms of c-kit activation in malignant cells have been described: acquisition of activating mutations or autocrine or paracrine stimulation of the receptor by its ligand SCF (27).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the production of HER2 heterodimers increases the affinity of other members of the family for their respective ligands (Citri, Yarden, 2006). HER3 does not have intrinsic tyrosine kinase activity, and it generates inactive HER3/HER3 dimers, but it can form heterodimers and be phosphorylated by HER2 or HER4 when activated by HER3 ligands (neuregulin 1 and 2) (Yarden, Sliwkowsk, 2001;Vlahovic, Crawford, 2003;Marmor, Skaria, Yarden, 2004). Although it is accepted that HER3 lacks functional residues (including aspartate catalytic action), studies have suggested that it conserves its capacity to phosphorylate its own intracellular domain (Shi et al, 2010).…”
Section: Human Epidermal Receptors: Tyrosine Kinase Structure Ligandmentioning
confidence: 99%
“…Tumor tissues were collected in serum-free Hanks' balanced salt solution (HBSS) medium and immediately processed for transplantation. The tumor specimens were cut into small fragments (5 mm 3 ) and kept in a Petri dish containing physiological saline. The tissue fragments were implanted bilaterally into 6-week old NOG mice.…”
Section: Primary Culture and Evaluation Of Tumor Forming Abilitymentioning
confidence: 99%
“…Growth factors, hormones, Matrigel and other supplements were not used. Drug administration was initiated when tumors in each group achieved an average volume of 120-350 mm 3 . Mice were randomly allocated to control and treatment groups.…”
Section: Assessment Of Imatinib Sensitivity Of the Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation